Government cloud procurement : contracts, data protection, and the quest for compliance - McGillivray, Kevin (Cambridge : Cambridge University Press, 2022)
In Government Cloud Procurement, Kevin McGillivray explores the question of whether governments can adopt cloud computing services and still meet their legal requirements and other obligations to citizens. The book focuses on the interplay between the technical properties of cloud computing services and the complex legal requirements applicable to cloud adoption and use. The legal issues evaluated include data privacy law (GDPR and the US regime), jurisdictional issues, contracts, and transnational private law approaches to addressing legal requirements. McGillivray also addresses the unique position of governments when they outsource core aspects of their information and communications technology to cloud service providers. His analysis is supported by extensive research examining actual cloud contracts obtained through Freedom of Information Act requests. With the demand for cloud computing on the rise, this study fills a gap in legal literature and offers guidance to organizations considering cloud computing.
Title from publisher's bibliographic system (viewed on 10 Dec 2021).
Keywords: Cloud computing -- Law and legislation; Data protection -- Law and legislation; Cloud computing -- Government policy; Cloud computing -- Purchasing